Starch digestibility and β-carotene bioaccessibility in the orange- fleshed sweet potato puree-wheat bread - Mbogo, D.; Muzhingi, T.; Janaswamy, S. (Wiley, 2021)
Vitamin A is essential for vision, human health, growth, immune function, and reproduction. Its deficiency leads to anemia, xerophthalmia, and growth reduction in children. Foods enriched with naturally occurring carotenes have the potential, in this regard, and orange‐fleshed sweet potato (OFSP) stands out tall as it is rich in β‐carotene (βC), a provitamin A carotenoid. In view of developing OFSP‐based functional foods to address the vitamin A deficiency (VAD) issues, herein, OFSP puree‐wheat composite breads have been prepared at 10% to 50% OFSP puree concentrations and bioaccessibility of βC has been estimated. The total βC is found to be 4.3, 9.2, 16.5, 23.3, and 33.6 µg/g in 10, 20, 30, 40, and 50% OFSP bread, respectively. The corresponding calculated retinol activity equivalents (RAE) are 30.9, 66.4, 119.5, 170.4, and 246.2 RAE/100 g. The efficiency of micellarization of all‐trans‐βC, 13‐cis βC, and 9‐cis βC after simulated oral, gastric, and small intestinal digestion are 1.4% to 6.4%, 1.4% to 7.2%, and 1.1% to 6.9%, respectively. The amount of micellarized βC correlates linearly with the OFSP concentration in the bread. Furthermore, in vitro starch digestion decreases with significant reduction in the Rapidly Digestible Starch (RDS) amount coupled with increase in the Slowly Digestible Starch (SDS) and Resistant Starch (RS) fractions. Overall, OFSP‐wheat composite bread holds adequate amount of provitamin A carotenoids. The amount of bioaccessible βC coupled with altered starch digestion of the OFSP wheat breads highlight their usefulness as novel functional foods that could address the VAD as well as glycemic issues toward improving human health.